Spotlight on researcher decisions: Infrastructure evaluation, instrumental variables, and specification screening - Jörg Ankel-Peters; Gunther Bensch; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
This paper revisits the instrumental variable (IV) approach in Lipscomb et al. (2013, 2021, LMB) to study the impacts of electrification. We first make corrections to the construction of the dataset, including the modelled IV. Revised estimates on main outcomes and mechanisms are statistically insignificant, with substantially lower effect sizes. We second develop a framework that accounts for weak IVs and discourages specification screening. Applying it to LMB, we find that most theoretically justified specifications yield insignificant results. The proposed framework is transferable to other IV applications to reduce potential bias stemming from researcher's or replicator's discretion. – – In diesem Papier replizieren wir den Instrumentvariablen-Ansatz (IV) von Lipscomb et al. (2013, 2021) zur Untersuchung der Wirkungen von Elektrifizierung. Wir nehmen zunächst Korrekturen an der Konstruktion des Datensatzes vor, einschließlich der modellierten IV. Die revidierten Schätzungen für die wichtigsten Ergebnisse und Mechanismen der Studie sind statistisch nicht signifikant, mit wesentlich geringeren Effektgrößen. Zweitens entwickeln wir einen Analyserahmen, der schwache IVs berücksichtigt und es erleichtert, Spezifikations-Screening zu vermeiden. Wir stellen bei der Anwendung dieses Analyserahmens fest, dass die meisten theoretisch berechtigten Spezifikationen im Falle von Lipscomb et al. nicht signifikante Ergebnisse liefern. Der vorgeschlagene Analyse-Rahmen ist auf andere Arten von IV-Anwendungen übertragbar, um potenzielle Verzerrungen aufgrund von Ermessensspielräumen auf Seiten der Forschenden und auch Replikatoren zu reduzieren.
Keywords: O13; C52; O18; 330; Replication; instrumental variables; electrification; infrastructure; specification curveanalysis; robust inference